أصداء القضية الفلسطينية في جريدة الأسبوع التونسية - تواتي إبراهيم, حمزة; تامه,بوبكر (University of Eloued جامعة الوادي, 2024)
فيعام 1922،وضعتعصبةالأممفلسطينوالتيكانتمنبينالأراضيالعثمانيةالسابقةتحتإدارةالمملكةالمتحدة. وأصبحتجميعهذهالأراضيفينهايةالمطافدولمستقلةتماماباستثناءفلسطين،فبالإضافةإلى "تقديمالمساعدةوالمشورةالإدارية"،دمجالانتدابالبريطاني "إعلانبلفور" لعام 1917،معرباعنتأييدهلإنشاءوطنقوميللشعباليهوديفيفلسطين". وخلالفترةالانتدابمن 1922 إلى 1947،حدثتهجرةيهوديةواسعةالنطاقمعظمهاقدمتمنأوروباالشرقية،وتضاعفتهذهالأرقامفيالثلاثيناتنتيجةالاضطهادالنازي. ونتجعنالمطالبالعربيةالتينادتبالاستقلالومقاومةالهجرةتمردعام 1937،وتلاهاستمرارالإرهابوالعنفمنالجانبين. وحاولتالمملكةالمتحدةبتحقيقالاستقلالفيأرضمزقتهاأعمالالعنفمنخلالبجريبصيغمختلفة. وفيعام 1947،حولتالمملكةالمتحدةمشكلةفلسطينإلىالأممالمتحدة. بعدالنظرفيبدائلأخرى،اقترحتالأممالمتحدةمنخلالقرارها 181 (أ) لعام 1947 إلىإنهاءالانتدابالبريطانيوتقسيمفلسطينإلىدولتينمستقلتين،واحدةعربيةفلسطينية،والأخرىيهودية،معتدويلالقدس. وقامتدولةواحدةبالإعلانعناستقلالهاكدولةإسرائيل،وفيحربهاعام 1948 معالدولالعربيةالمجاورةوتوسعتهذهالدولةلتشملعلى 77 فيالمائةمنأراضيفلسطين،بمافيذلكالجزءالأكبرمنالقدس. ونتيجةذلك،فرأكثرمننصفالسكانالعربالفلسطينيينأوطردوا. وسيطرتالأردنومصرعلىبقيةالأراضيالتيحددهاالقرار 181 للدولةالعربية. Abstract In 1922, the League of Nations placed Palestine, whichwasamong the former Ottoman territories, under United Kingdom administration. All of theseterritorieseventuallybecamecompletelyindependent states except Palestine, and in addition to "providing administrative assistance and advice", the British Mandate incorporated the Balfour Declaration of 1917, expressingits support for the establishment of a national homeland for the Jewish people in Palestine. During the Mandate periodfrom 1922 to 1947, therewas large-scaleJewish immigration, most of which came fromEastern Europe, and thesenumbersdoubled in the 1930s as a result of Nazi persecution. Arabdemands for independence and resistance to immigration resulted in the 1937 rebellion, followed by continuedterrorism and violence on bothsides. The United Kingdomattempted to achieveindependence in a land torn by violence throughvarious formulas. In 1947, the United Kingdomreferred the Palestine problem to the United Nations. Afterconsideringother alternatives, the United Nations, throughitsresolution 181 (a) of 1947, proposedending the British Mandate and dividing Palestine intotwoindependent states, one Arab-Palestinian and the otherJewish, with the internationalization of Jerusalem. One state declareditsindependence as the State of Israel, and in its 1948 warwithneighboringArab countries, this state expanded to include 77 percent of the territory of Palestine, including the largest part of Jerusalem. As a result, more thanhalf of the PalestinianArab population fled or wasexpelled. Jordan and Egyptcontrolled the rest of the lands specified by Resolution 181 for the Arab state
1945-1956م
Keywords: القضيةالفلسطينية; جريدةالأسبوع التونسية; Palestinian issue; Tunisian Al-Usbunewspaper; media